2015
DOI: 10.1177/0267659115588634
|View full text |Cite
|
Sign up to set email alerts
|

Minimized extracorporeal circulation is improving outcome of coronary artery bypass surgery in the elderly

Abstract: Advanced age is a known risk factor for morbidity and mortality after coronary artery bypass grafting (CABG). Minimized extracorporeal circulation (MECC) has been shown to reduce the negative effects associated with conventional extracorporeal circulation (CECC). This trial assesses the impact of MECC on the outcome of elderly patients undergoing CABG. Eight hundred and seventy-five patients (mean age 78.35 years) underwent isolated CABG using CECC (n=345) or MECC (n=530). The MECC group had a significantly sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
5
0
4
Order By: Relevance
“…There is some literature highlighting that elderly patients are more susceptible to the adverse effects of CPB, and that MiECC may offer even more advantage to this group of patients undergoing CABG. 21,22 Another meta-analysis performed by Anastasiadis et al reported similar findings, observing that MiECC was associated with a significantly reduced mortality and morbidity. 23 Furthermore, this study was able to demonstrate a reduced inflammatory response and improved myocardial preservation (reduced postoperative troponin) in the MiECC cohort.…”
Section: Discussionmentioning
confidence: 68%
“…There is some literature highlighting that elderly patients are more susceptible to the adverse effects of CPB, and that MiECC may offer even more advantage to this group of patients undergoing CABG. 21,22 Another meta-analysis performed by Anastasiadis et al reported similar findings, observing that MiECC was associated with a significantly reduced mortality and morbidity. 23 Furthermore, this study was able to demonstrate a reduced inflammatory response and improved myocardial preservation (reduced postoperative troponin) in the MiECC cohort.…”
Section: Discussionmentioning
confidence: 68%
“…En este estudio se identificó que no hubo diferencias en el nivel de independencia funcional de los pacientes después de la cirugía relacionándola con la variable de uso de circulación extra-corpórea diferente a lo encontrado por Curzel et al (6) quienes demu estran que a mayor tiempo de circulación extracorpórea menor puntaje en la escala de medida de independencia funcional; esto puede estar relacionado con la poca variabilidad en los tiempos de cirugía,así como al desconocimiento por parte de los profesionales sobre los efectos negativos de la circulación extracórporea, que pueden tener incidencia en el acto quirúrgico y por ende en el menor tiempo de exposición a este procedimiento (31).…”
Section: Discussionunclassified
“…При аортокоронарном шунтировании [52] и протезировании аортального клапана в условиях MiECC отмечается более короткое время перфузии [15]. По данным K. Anastasiadis и соавт., время перфузии составляет 102,9 ± 25,0 мин при использовании миниинвазивного контура против 122,2 ± 33,0 мин при использовании стандартного ЭКК (р<0,001) [4].…”
Section: преимущества системunclassified
“…Использование MiECC имеет преимущество у пациентов высокого риска: старшей возрастной группы и пожилых, с сахарным диабетом, предоперационной анемией, синдромом малого сердечного выброса, предполагаемым длительным ИК и другими категориями высокого риска [10,41,43,[52][53][54].…”
Section: преимущества системunclassified
See 1 more Smart Citation